2004
DOI: 10.1021/pr049940z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 70S Ribosome from Rhodopseudomonas palustris Using an Integrated “Top-Down” and “Bottom-Up” Mass Spectrometric Approach

Abstract: We present a comprehensive mass spectrometric approach that integrates intact protein molecular mass measurement ("top-down") and proteolytic fragment identification ("bottom-up") to characterize the 70S ribosome from Rhodopseudomonas palustris. Forty-two intact protein identifications were obtained by the top-down approach and 53 out of the 54 orthologs to Escherichia coli ribosomal proteins were identified from bottom-up analysis. This integrated approach simplified the assignment of post-translational modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 66 publications
4
119
0
Order By: Relevance
“…Proteomic studies of bacterial ribosomal proteins have reported di-or monomethylation at this residue in E. coli (29), Caulobacter crescentus (28), and Rhodopseudomonas palustris (27), and the reported molecular mass of Thermus thermophilus RpL7/L12 also suggests methylation (26). However, this modification appears not to be present in all bacteria as Bacillus subtilis RpL7/L12 was found to be unmodified (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic studies of bacterial ribosomal proteins have reported di-or monomethylation at this residue in E. coli (29), Caulobacter crescentus (28), and Rhodopseudomonas palustris (27), and the reported molecular mass of Thermus thermophilus RpL7/L12 also suggests methylation (26). However, this modification appears not to be present in all bacteria as Bacillus subtilis RpL7/L12 was found to be unmodified (45).…”
Section: Discussionmentioning
confidence: 99%
“…particles were isolated from A. tumefaciens cells at 4°C following a previously published procedure (27) with some modifications. Cells were lysed in Ribosome Isolation Buffer (20 mM Tris-HCl, pH 7.5, 50 mM magnesium acetate, 100 mM NH 4 Cl, 1 mM EDTA) supplemented with fresh 2 mM DTT, 1 unit/ml DNase I (Qiagen), and 1ϫ Complete (EDTA-free) protease inhibitor mixture and sonicated.…”
Section: Isolation Of Ribosomes From a Tumefaciens Cells-ribosomalmentioning
confidence: 99%
“…Covalent Modifications of Arabidopsis Cytosolic Ribosomal Proteins-Covalent protein modifications such as acetylation, methylation, and phosphorylation have emerged as potentially being important factors contributing to ribosomal heterogeneity in both eukaryotes (4,19,26,27) and prokaryotes (28,29). In the ribosomes of higher plants, studying the role of covalent r-protein modification in ribosomal heterogeneity is complicated by the frequent expression of relatively high (compared with other classes of organism) numbers of different, yet often highly conserved isoforms of each ribosomal subunit.…”
Section: Non-ribosomal Proteins Bound Tomentioning
confidence: 99%
“…In addition to heterogeneity derived from different ribosomal genes for the same subunit, covalent modification introduces further potential differences in ribosomal protein structure and function. Covalent modifications of ribosomal proteins have been reported in bacteria (28,29,(31)(32)(33)(34)(35), fungi (3, 4, 8, 36 -38), mammals (5)(6)(7)39), and plants (19). However, in almost all of these studies, limitations of the techniques used, such as peptide mass fingerprinting, topdown MS analysis of intact r-proteins, and acid hydrolysis to remove rRNA, have precluded detection of acid/base-labile, low stoichiometry, or difficult-to-detect modifications or the determination of precise details about the exact position(s) and structure(s) of the modified residue(s).…”
Section: Covalent Modifications Of Arabidopsis 80 S Ribosomal Proteinmentioning
confidence: 99%
“…70S ribosomes from R. palustris were purified and fractionated using a high salt sucrose cushion and sucrose density fractionation as previously described [18]. Acid extracted [19] ribosomal proteins were denatured and reduced in 6 M guanidine HCl, 50 mM Tris-HCl (pH 7.6), with 10 mM DTT at 60°C for 45 min.…”
Section: Preparation and Lc-ms-ms Analysis Of Protein Standard Mixturmentioning
confidence: 99%